Spirit Pembebasan dalam Hukum Islam - Abu Yazid Adnan Quthny (Asy-Syari’ah : Jurnal Hukum Islam, 2017)
The urgency of implementing Islamic law for the creation of principles of justice is now a complicated issue in the global era. The high intervention of the investors and the western nations in building the world economic map, not infrequently sacrifice the value of justice in the life of a society. The high social imbalance between the poor and the rich, the spread of a free-standing culture that ended with the abortion behavior of teenagers, has made various problems unending. Islamic law that should be a solution in various aspects of community life, gradually unable to be implemented in the realm of community life due to various conflicts of interest. While multiculturalism is occurring in some areas, it is often used as an alibi for some societies to reject Islamic law as an integral part of the human struggle free from injustice in all things. Not infrequently, people who are keen to fight for Islamic law in a society are regarded as extremist groups.